Leadership styles and work performance in nurses working in the Health Sector, Juliaca 2019 - Yallercco Quispe, Luz (2020)
Objective: to determine the relationship between leadership style and job performance in nurseswho work in the Health Sector of Juliaca. Methodology: design was non-experimental, descriptive,correlational and cross-sectional. The sample was made up of 120 nursing professionals. Three Likertscale instruments were applied for data collection. Results: there is no significant relationship betweenboth variables (p value 0.555), according to the Kendall Tau-b test. Likewise, 74.2% of the nurses have atransformational leadership and 84.2% showed regular work performance during the study. Conclusion:leadership style is not related to job performance in nurses working in the Health Sector.